Habituation of Discipline Characters at SMP Muhammadiyah 6 Krian During the Covid-19 Pandemic - Pintan Susilo Putri; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
Character is something that cannot be built easily only by teaching the theory of values contained but also dominantly must be practiced in everyday life. Discipline is one of the characters that will be discussed this time. Judging from the current phenomenon, namely the impact of online learning during the Covid-19 pandemic, the habituation of disciplined characters that had previously become a habit gradually faded, which also resulted in student learning outcomes. For example, there are often online delays to enter class, delays in submitting assignments, not participating in activities, or coloring hair. All of this requires proper handling and a balance of cooperation between teachers and parents is needed. In this phenomenon the author uses descriptive qualitative research methods, where this study collects data from interviews with informants and observes the behavior of a group is analyzed and then described by connecting theories with one another. The topic that the author is aiming for is the habituation of discipline in SMP Muhammadiyah 6 Krian students during the COVID-19 pandemic What handling and habits are applied to regenerate the impact caused by Covid-19.